The Relationship Between Regular Consumption of Fe Tablets and the Incidence of Anemia in Pregnant Women in the Third Trimester of Pregnancy in the Jombang-Jember Community Health Center Service Area - Dian Dhurotul Maftukha; Susilawati Susilawati; Eni Subiastutik (Sean Institute, 2025)
In all nations, including Indonesia, anemia during pregnancy is a serious issue for expectant mothers. Due to poor regular ingestion of iron, pregnant women suffer from anemia. According to Riskesdas, 37.1% of Indonesian pregnant women suffered from anemia in 2020. 5.8% of people in East Java Province suffered from anemia. In 2017, 10.42% of pregnant women in Jember Regency and 47.993% of pregnant women in Jombang District had anemia. According to Dolang (2020), anemia affects 25.0% of people who do not frequently take iron tablets and 74.5% of people who do not regularly take iron supplements. Goal: to ascertain if frequent use of iron supplements and the incidence of anemia during the third trimester of pregnancy are connected. This study employs a correlational technique and an analytical research strategy. Using a proportionate random sampling approach, 42 pregnant women made up the sample, whereas 47 pregnant women made up the population in this study. Analyzing data with Fisher's exact test. The results of the study showed that 13 (31.0%) of the individuals did not regularly use iron supplements, whereas 29 (69.0%) did. Twenty (48.0%) of the people did not have anemia, whereas 22 (52.0%) did. Fisher's exact test findings revealed a p-value of 0.01 < 0.05. The prevalence of anemia during the third trimester of pregnancy is significantly correlated with the regular use of iron supplements. In conclusion, anemia is more common in women who do not regularly take Fe pills than in mothers who do. To promote the rise in Fe pills, pregnant women must take them consistently every day and have a healthy diet.